Flavonoids and Aging - Nasihun, Taufiqurrachman (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2016)
Aging is inevitable process, however human comes into aging is in difference way and difference rates. Some of them undergo aging earlier due to degenerative diseases, unable to reach the maximum lifespan and are thus denominated secondary aging (Huebschmann AG, 2011). Some of others undergo aging latter, looked younger than their truely chronological age, have no suffer degenerative disease, able to achieve maximum lifespan and so called primary aging (De la Fuente, 2009; Huebschmann AG, 2011). Maximum lifespan or often called longevity of the species is defined as maximum time that a species belonging to determine how long the species can live, for example maximum lifespan in human beings is 122 years, whereas the lifespan in rats and mouse strains is only 3 and 4 years respectively (De lafuente, 2009). It must be distinguished this longevity from mean or averages longevity. Average longevity can be defined as the average of time that member of population that have been born on the same date live (De la Fuente, 2009). The maximum lifespan is fixed in each species, meanwhile the lifespan of individual subject in the population, even when their genotype are the same and grow in a common environment condition, such as protected from external hazard show marked variability (Kirkwood, 2005).